2002
DOI: 10.1093/emboj/cdf629
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M regulates membrane traffic and stimulates bile canalicular membrane biogenesis in HepG2 cells

Abstract: Hepatocytes are the major epithelial cells of the liver and they display membrane polarity: the sinusoidal membrane representing the basolateral surface, while the bile canalicular membrane is typical of the apical membrane. In polarized HepG2 cells an endosomal organelle, SAC, fulfills a prominent role in the biogenesis of the canalicular membrane, reflected by its ability to sort and redistribute apical and basolateral sphingolipids. Here we show that SAC appears to be a crucial target for a cytokine‐induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 28 publications
(57 reference statements)
2
32
0
Order By: Relevance
“…Indeed, we have previously shown that OSM activates a vesicular membrane trafficking pathway from SAC to the apical PM, which is dependent on cAMP/PKA activity (van der Wouden et al, 2002). Importantly, activation of this OSM-cAMP/PKA-regulated pathway is crucial for apical PM biogenesis in HepG2 cells (van der Wouden et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Indeed, we have previously shown that OSM activates a vesicular membrane trafficking pathway from SAC to the apical PM, which is dependent on cAMP/PKA activity (van der Wouden et al, 2002). Importantly, activation of this OSM-cAMP/PKA-regulated pathway is crucial for apical PM biogenesis in HepG2 cells (van der Wouden et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, OSM induces adherens junction formation by altering the subcellular localization of adherens junction components, including E-cadherin and catenins (Matsui et al, 2002). In human fetal hepatocytes as well as in welldifferentiated human hepatic HepG2 cells, OSM stimulates the development of apical bile canalicular plasma membrane (PM) domains (Lazaro et al, 2003;van der Wouden et al, 2002), which requires the activation of a gp130-mediated signaling cascade and endogenous protein kinase A (PKA) activity (van der Wouden et al, 2002). Although the molecular mechanisms that underlie apicalization of the cell surface in hepatocytes are poorly understood, the de novo reorganization of the lateral PM after the establishment of E-cadherin-dependent cell-cell adhesion, mediated by cytoskeleton rearrangements and the polarized sorting and trafficking of proteins and lipids, plays a crucial role.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations